The Criminal Liability of Human Trafficking within the Framework of Transnational Organized Crime - Vaula Karera; Wefy Efticha Sary (The Future of Education Journal, 2026)
Human trafficking is a form of transnational organized crime that has serious impacts on human rights and requires effective criminal accountability. The legal issue examined in this study focuses on the regulation of criminal liability for perpetrators and the mechanisms of law enforcement within the framework of international criminal law. This study aims to analyze the forms of criminal liability in human trafficking crimes and to examine the mechanisms for their implementation against organized criminal networks. The research employed a normative juridical method using statutory and conceptual approaches, supported by library research. The findings indicate that criminal liability applies not only to the principal perpetrators but also to all parties involved in the criminal network, including corporations. In addition, law enforcement requires international cooperation mechanisms such as extradition and mutual legal assistance, although practical challenges remain in terms of evidence collection and coordination among states.